BUDIDAYA SAPI SONOK DI KECAMATAN WARU – PAMEKASAN - Desi Kurniati Agustina (MADURANCH: Jurnal Ilmu Peternakan, 2011)
The research was conducted on the basis of the researcher's curiosity about the development effort Sonok cow. Cattle Sonok not just a hobby and something that prestige but would be profitable if packaged or in creative concept in its development. The study used a descriptive exploratory approach. The results showed that the development of cattle farming Sonok increasingly growing, concern was triggered by cattle ranchers to continue to preserve cultural Sonok cow sonok through frequent holding of the contest, to lift cow sale value of Madura. Intensive maintenance Sonok cow in cattle and institutional Sonok already neatly with the Society